2019
DOI: 10.1007/s00707-019-02434-7
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent single-layer models in deformation analysis of laminated multilayered plates

Abstract: The performance of selected equivalent single-layer (ESL) models is evaluated within several classical benchmark tests for linear static analysis of multilayered plates. The authors developed their own finite element software based on the first-order shear deformation theory (FOSD) with some modifications incorporated including a correction of the transverse shear stiffness and an application of zigzag-type functions. Seven different ESL models were considered in the study; beside the classical FOSD model, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Since thin PET diaphragms are usually transparent, it is necessary to coat a certain thickness of metal reflector on the diaphragm to increase its optical reflectivity. Considering the effect of the metal reflector on the mechanical response of the diaphragm, PET diaphragms coated with different thicknesses of metal reflector were simulated using the equivalent single layer theory [ 31 ]. In this simulation, the metal reflector used is gold, and its density is 19,300 kg/m 3 .…”
Section: Principle and Designmentioning
confidence: 99%
“…Since thin PET diaphragms are usually transparent, it is necessary to coat a certain thickness of metal reflector on the diaphragm to increase its optical reflectivity. Considering the effect of the metal reflector on the mechanical response of the diaphragm, PET diaphragms coated with different thicknesses of metal reflector were simulated using the equivalent single layer theory [ 31 ]. In this simulation, the metal reflector used is gold, and its density is 19,300 kg/m 3 .…”
Section: Principle and Designmentioning
confidence: 99%
“…where the symbols of double summations will be omitted in the later work of this paper for brevity. Substituting Equations (13) and (14) in (10), the authors can obtain…”
Section: Heat Conduction Analysismentioning
confidence: 99%
“…The above-mentioned theories can be categorized as the two-dimensional (2D) equivalent single layer theories (ESLTs) based on the principle of virtual displacements (PVD), rather than the Reissner mixed variational theorem (RMVT). In addition, Kreja and Sabik [10] evaluated the performance of some selected ESLTs by comparing their solutions with several benchmark solutions for the static problems of multilayered plates.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous examples, the standard RZT has demonstrated to be very accurate for cross-ply laminated and sandwich plates. Recently, Kreja and Sabik [34] showed that it is not possible to study multilayered angle-ply plates in which two adjacent layers have alternating orientations but the same absolute value. Due to the derivation of zigzag functions in the standard RZT for these lamination schemes, the slope of zigzag functions is constant for each layer and, in order to satisfy the null value for these functions at the external surfaces, it results in that they are constant and null through-the-thickness.…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the drawback of the standard RZT for some lay-ups highlighted by Kreja and Sabik [34] and to implement a further mathematical tool for the study of general laminates, Sorrenti and Di Sciuva [42] reformulated the standard Refined Zigzag Theory by introducing new zigzag functions in the local contribution. The newly developed model, named the enhanced RZT (en-RZT), has shown excellent predictive capabilities in [42] for the bending response of angle-ply multilayered laminate plates.…”
Section: Introductionmentioning
confidence: 99%